Design of a rapid screening technique for identification of Shewanella Oneidensis nitrate-reductant deficient mutants - Umi Nor Zarina Othman (2016)
Shewanella oneidensisis is an important model organism for bioremediation studies and electrical generation because of its diverse respiratory capabilities, conferred in part by multicomponent, branched electron transport systems. A rapid mutant screening technique was developed to identify S. oneidensis MR-1 respiratory mutants unable to reduce Nitrate (N0₃) as anaerobic electron acceptor. S.oneidensis nitrate-reductant deficient mutants screening technique was based on the observation that wild-type S. oneidensis produced a red precipitate on its colony surface during screening test, while colonies arising from mutagenized cells did not changed the color at all. The cell density of mutagenized cells 0.2396 (±.152) is lower compared to wild type control 0.3318 (±.576). This report describes the design of rapid screening technique and its application to identify mutants in a metal-reducing member of the genus Shewanella.